In Silico Toxicology – Non-Testing Methods - Raunio, Hannu (Frontiers in Pharmacology, 2011)
In silico toxicology in its broadest sense means “anything that we can do with a computer in toxicology”. Many different types of in silico methods have been developed to characterise and predict toxic outcomes in humans and environment. The term non-testing methods denote grouping approaches, structure-activity relationship (SAR), and expert systems. These methods are already used for regulatory purposes and it is anticipated that their role will be much more prominent in the near future. This Perspective will delineate the basic principles of non-testing methods and evaluate their role in current and future risk assessment of chemical compounds.